Competition‐driven build‐up of habitat isolation and selection favoring modified dispersal patterns in a young avian hybrid zone. (22nd August 2016) - Rybinski, Jakub; Sirkiä, Päivi M.; McFarlane, S. Eryn; Vallin, Niclas; Wheatcroft, David; Ålund, Murielle; Qvarnström, Anna
Abstract : Competition‐driven evolution of habitat isolation is an important mechanism of ecological speciation but empirical support for this process is often indirect. We examined how an on‐going displacement of pied flycatchers from their preferred breeding habitat by collared flycatchers in a young secondary contact zone is associated with (a) access to an important food resource (caterpillar larvae), (b) immigration of pied flycatchers in relation to habitat quality, and (c) the risk of hybridization in relation to habitat quality. Over the past 12 years, the estimated access to caterpillar larvae biomass in the habitat surrounding the nests of pied flycatchers has decreased by a fifth due to shifted establishment possibilities, especially for immigrants. However, breeding in the high quality habitat has become associated with such a high risk of hybridization for pied flycatchers that overall selection currently favors pied flycatchers that were forced to immigrate into the poorer habitats (despite lower access to preferred food items). Our results show that competition‐driven habitat segregation can lead to fast habitat isolation, which per se caused an opportunity for selection to act in favor of future "voluntarily" altered immigration patterns and possibly strengthened habitat isolation through reinforcement.